Evaluasi Kriteria Pemilihan Supplier Material Auxiliary Engine Shipyard Menggunakan Metode Cut-off point - Santika Sari; Rizqi Mubaroq (Performa: Media Ilmiah Teknik Industri, 2023)
Supplier selection is one of the most important activities for increasing the company's effectiveness and efficiency in supplying raw materials from suppliers. In this study, problems were found in the procurement of auxiliary engine material, which is one of the most important materials in the long-term part of the ship, which is carried out every 1-2 years with a level of ordering 10 to 20 materials per message to avoid errors in the supplier selection criteria. This study aims to determine and identify the criteria and sub-criteria for consideration used in the selection of suppliers. The study uses the Cut-off point method to evaluate supplier criteria. Based on the calculation results of the natural Cut-off point obtained each criteria and sub-criteria as follows: price: X11; quality: X21, and X23; shipping: X33 and X34; response: X41 and X42; and services: X52, X53, and X54. Obtained results from 20 sub-criteria to 10 sub-criteria that are of concern and relevance to the company in the selection of suppliers of auxiliary engine shipyard materials